R. K. Narayan’s (Post-)Colonial Perspective: Malgudi in Its Humour (University of Bucharest Review. Literary and Cultural Studies Series, 2025)
R. K. Narayan (1906-2001) is considered one of the founding fathers of Indian writing in English, along with Raja Rao, Mulk Raj Anand and G.V. Desani, and is best known for creating the imaginary town of Malgudi. Another important feature of his fiction is what both critics and readers call a gentle or light-hearted humour. Humour has often been used to both subvert and survive various forms of political oppression (see Ştefănescu, Tripathi and Chettri). In Narayan, Malgudi, the centre of the action, is both a colonial and a post-colonial town, created and recreated over years and even decades. Since Malgudi can be considered a metonymy of India (see Mukherjee), Narayan’s use of humour as a subversive device, together with his skilful examination of the cultural and colonial context, can be perceived as a poignant criticism of the British colonial system and what it entailed, specifically the suppression of what constitutes ‘Indianness’, the Indian way of life and cultural values. On the other hand, the light-hearted and subversive irony allows Narayan to offer a more profound insight into the human nature as such, while juxtaposing a colonial and post-colonial context.